PERTANIAN KONSERVASI UNTUK MENGURANGI DAMPAK PERUBAHAN IKLIM DAN MENINGKATKAN PRODUKTIVITAS TANAMAN DI TAMAN NASIONAL GUNUNG HALIMUN-SALAK - Marningot Tua Natalis Situmorang; Yossa Istiadi (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
ABSTRACT Conservation agriculture is an approach developed to enhance the resilience of agricultural systems to climate change while simultaneously improving productivity and the welfare of rural communities. This study aims to analyze the factors influencing the adoption of conservation agriculture practices and to assess their impact on farmers’ productivity in areas surrounding Mount Halimun-Salak National Park. The research data were obtained through a household survey of farmers and analyzed using an econometric approach with the Multinomial Endogenous Switching Regression (MESR) model to identify the determinants of adoption and to compare the productivity of farmers who adopt and those who do not adopt these practices. The results indicate that several socio-economic characteristics significantly influence farmers’ adoption decisions, including age, gender, farming experience, land size, level of formal education, access to extension services, and membership in farmer organizations or associations. Furthermore, the implementation of combined conservation agriculture practices has been shown to have a positive effect on increasing farmers’ productivity and income compared to conventional farming systems. These findings suggest that the development of conservation agriculture practices can serve as an effective adaptation strategy to address climate change while improving the performance of the agricultural sector at the local level. Therefore, policy support and active involvement from stakeholders are needed to expand farmers’ access to information, extension services, and institutional support in order to encourage the broader and sustainable adoption of conservation agriculture practices. ABSTRAK Pertanian konservasi merupakan salah satu pendekatan yang dikembangkan untuk meningkatkan ketahanan sistem pertanian terhadap perubahan iklim sekaligus meningkatkan produktivitas dan kesejahteraan masyarakat pedesaan. Penelitian ini bertujuan untuk menganalisis faktor-faktor yang mempengaruhi adopsi praktik pertanian konservasi serta menilai dampaknya terhadap produktivitas petani di kawasan sekitar Taman Nasional Gunung Halimun-Salak. Data penelitian diperoleh melalui survei rumah tangga petani, kemudian dianalisis menggunakan pendekatan ekonometrika dengan model Multinomial Endogenous Switching Regression (MESR) untuk mengidentifikasi determinan adopsi serta membandingkan produktivitas antara petani yang mengadopsi dan yang tidak mengadopsi praktik tersebut. Hasil analisis menunjukkan bahwa beberapa karakteristik sosial ekonomi petani berpengaruh signifikan terhadap keputusan adopsi, antara lain usia, jenis kelamin, pengalaman bertani, luas lahan, tingkat pendidikan formal, akses terhadap layanan penyuluhan, serta keanggotaan dalam organisasi atau asosiasi petani. Selain itu, penerapan kombinasi praktik pertanian konservasi terbukti memberikan dampak positif terhadap peningkatan produktivitas dan pendapatan petani dibandingkan dengan sistem budidaya konvensional. Temuan ini menunjukkan bahwa pengembangan praktik pertanian konservasi dapat menjadi strategi adaptasi yang efektif dalam menghadapi perubahan iklim sekaligus meningkatkan kinerja sektor pertanian di tingkat lokal. Oleh karena itu, diperlukan dukungan kebijakan dan peran aktif pemangku kepentingan dalam memperluas akses petani terhadap informasi, penyuluhan, serta kelembagaan yang dapat mendorong peningkatan adopsi praktik pertanian konservasi secara berkelanjutan.